2022
DOI: 10.1111/ele.14153
|View full text |Cite
|
Sign up to set email alerts
|

Linking human impacts to community processes in terrestrial and freshwater ecosystems

Abstract: Human impacts such as habitat loss, climate change and biological invasions are radically altering biodiversity, with greater effects projected into the future. Evidence suggests human impacts may differ substantially between terrestrial and freshwater ecosystems, but the reasons for these differences are poorly understood. We propose an integrative approach to explain these differences by linking impacts to four fundamental processes that structure communities: dispersal, speciation, species-level selection a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 170 publications
(244 reference statements)
0
9
0
Order By: Relevance
“…This may be because drivers differ in importance between regions. In addition, interconnections between realms or habitats make the effect of drivers context-dependent [ 55 , 56 ]. In one study, only 60% of co-occurring arthropod taxa at order level showed trends in the same direction [ 54 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…This may be because drivers differ in importance between regions. In addition, interconnections between realms or habitats make the effect of drivers context-dependent [ 55 , 56 ]. In one study, only 60% of co-occurring arthropod taxa at order level showed trends in the same direction [ 54 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Studies have shown that soil bacterial diversity increases or exhibits a unimodal pattern along latitude (Bahram et al., 2018), which is regulated by soil pH (Vasar et al., 2022). However, the intensity and extent of human activities will increase the challenge of unraveling the assembly mechanisms of agricultural soil biodiversity (McFadden et al., 2023). It is urgently needed to reveal the drivers of large‐scale spatial variation in agricultural biodiversity, which is essential for obtaining a mechanistic understanding of the origination and maintenance of agricultural biodiversity and predicting biodiversity loss from agricultural effects.…”
Section: Introductionmentioning
confidence: 99%
“…Different land cover types can have multiple, even contrasting, effects within the same system. The terrestrial system's influence on the aquatic fauna is not always straightforward or can display scale dependence (Ho et al, 2022; McFadden et al, 2023). For instance, agricultural land cover effects on river systems can have various results, ranging from water pollution and habitat fragmentation to changes within the riverbed structure and hydrological regimes (Dala‐Corte et al, 2016; Leitão et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On a larger scale, there is evidence of decreases in aquatic and terrestrial species richness and changes in communities in Amazonian tropical streams linked to increased deforestation in the upstream basins (Cantera et al, 2022). Poorer and more stochastic assemblages of organisms generally occur under high human pressure (McFadden et al, 2023;Vellend et al, 2007Vellend et al, , 2014Zeni et al, 2020). However, assemblage information across large river systems is not readily available, leading to a lack of data on species distribution in certain global regions (Davison et al, 2021) and within the river systems.…”
mentioning
confidence: 99%